Wireless laser communication system / Rasfan Zainal Abidin - Zainal Abidin, Rasfan (2000)
This thesis focuses on the design and development of a wireless laser communication system. Helium Neon class II laser was used to show that the free space laser beam can be used as a medium to transmit voice signal. The design, construction and test results obtained from each part of the system are adequately described. An overview of laser is also included. Suggestion on ways to improve the system for the actual implementation of a laser communication system are given at the end at the thesis.